Fabrication, characterization and in vitro biocompatibility of electrospun hydroxyethyl cellulose/poly (vinyl) alcohol nanofibrous composite biomaterial for bone tissue engineering - Chahal, Sugandha; Jahir Hussain, Fathima Shahitha; Anuj, Kumar; Abdull Rasad, Mohammad Syaiful Bahari; Mohd Yusoff, Mashitah (Elsevier, 2016)
Development of novel scaffold materials that mimic the extracellular matrix, architecturally and functionally, is becoming highly important to meet the demands of the advances in bone tissue engineering. This paper reports, the fabrication of natural polymer cellulose derived hydroxyethyl cellulose (HEC) based nanostructured scaffolds with uniform fiber morphology through electrospinning. Poly (vinyl alcohol) (PVA) was used as an ionic solvent for supporting the electrospinning of HEC. Scanning electron microscopy and ImageJ analysis revealed the formation of non-woven nanofibers with well-defined porous architecture. The interactions between HEC and PVA in the electrospun nanofibers were studied by differential scanning calorimetry, X-ray diffraction, dynamic mechanical analysis thermo-gravimetric analysis; Fourier transform-infrared spectroscopy, X-ray photoelectron spectroscopy and tensile test. The mechanical properties of scaffolds were significantly altered with different ratios of HEC/PVA. Further, the biocompatibility of HEC/PVA scaffolds was evaluated using human osteosarcoma cells. The SEM images revealed favorable cells attachment and spreading on the nanofibrous scaffolds and MTS assay showed increased cell proliferation after different time periods. Thus, these results indicate that HEC based nanofibrous scaffolds will be a promising candidate for bone tissue engineering.